Smart mating: the cognitive ability of females influences their preference for male cognitive ability. (22nd June 2021) - Álvarez-Quintero, Náyade; Velando, Alberto; Kim, Sin-Yeon
Abstract: Cognitive abilities may be crucial for individuals to respond appropriately to their social and natural environment, thereby increasing fitness. However, the role of cognitive traits in sexual selection has received relatively little attention. Here, we studied 1) whether male secondary sexual traits (colour, courtship, and nest) reflect their cognitive ability, 2) whether females choose mates based on males' and their own cognitive abilities, and 3) how the interplay between secondary sexual traits and cognitive ability determines male attractiveness in the three-spined stickleback ( Gasterosteus aculetaus ). For this, we first evaluated the cognitive ability of sexually mature males and females in a detour-reaching task. Then, female preference was repeatedly assessed in a dichotomous-choice test, where the female was exposed to two males with contrasting performances (relatively good and bad) in the detour-reaching task. Female preference for better performing males was affected by the female's own cognitive ability. Females with relatively medium-low cognitive ability preferred males with high ability, whereas females with high ability showed no preference. We also found that males with higher cognitive abilities built more elaborated nests, but showed weaker red nuptial colouration. To our knowledge, this is among the first results that illustrate how cognitive traits of both sexes influence female mate preference, which has implications for the strength and direction of sexual selection. Abstract : Cognition may aid in the development of behavioral sexual displays, thereby contributing to mating success. In this study, female sticklebacks with relatively low cognitive ability preferred mating with males with better cognitive ability, while those with high ability did not have preference for smart males. Male's cognitive ability was positively related to nest structure but negatively related to nuptial color. Our results show the complex interplay between secondary sexual traits and cognitive ability in sexual selection.